MENINGKATKAN MOTIVASI BELAJAR MENGENAL KONSEP ANGKA 1-5 BAGI ANAK DOWN SINDRUMO KELAS D1 / L1 DI SLB MUTIARA BUDI LUBUK ALUNG - Ramadhani - Fitri (Universitas Negeri Padang, 2013)
This research starts from outcome asessement which researchers conducted in Lubuk Alune Mutiara Budi SLB. against the child of Down Svndrome initials AB was 12 years old that is less interested or less motivated in learning to know the concept of numbers 1-5. Researchers want to improve motivation to learn to know the concept of numbers 1-5 children, this research aims to make the children Down Syndrome have high motivation in learning to know the concept of number of 1-5. In a hypothesis research stated that: A game sticker figures can increase the motivation learn to the concept of the number of 1-5 to the child of down syndrome AB. The kind of research used was the single subject research with a design A-B, namely comparing motivation to learn the child of Down Syndrome on condition baseline and the condition of treatment. Technique analysis of data used based on observation data in the form Of Visual Analysis Of The Charis. After the data is analyzed, then retrieved the results: the length of the condition of the to Six times observation for six days. While me lengths the condition of intervening ten times observation for ten days. The direction of the tendency of data baseline that is indicative of motivation learn the child in know the concept of the number of 1-5 child AB. Appointed a little ride (+), While the tendency ot data intervention is increased (+) in accordance with the expected. Of research results that analyzed includes the number of observations on condition the baseline as much as six times and kondisi treatment as much as ten times. The result of this research was shown on close analysis of data in conditions and analvsis of data between the condition of being showing the changes in the motivation learn to the concept of the number of 1-5 on child x toward what is better. Of revenue this data can be inferred that the game sticker figures can be used to increase me motivation iearn to the Concept of points for the child down syndrome 1st class. Advised for class teacher or teacher mathematics so as to be the use of the game sticker figures in learning to know the concept of the number of 1-5 to a child down syndrome.